PRE-SERVICE TEACHERS’ BELIEFS ABOUT TEACHING ESOL STUDENTS IN MAINSTREAM CLASSROOMS - Torres, Kelly; Tackett, Samantha (International Online Journal of Education and Teaching, 2016)
During the last several decades, there has been a dramatic increase in the number of English language learners (ELLs) entering American educational settings. One result in the changing demographics of K-12 settings is the stark contrast between the backgrounds of learners found in the classroom settings and their educators. This has resulted in many pre-service teachers being inadequately prepared to meet the unique learning needs of their future learners (Eisenhardt, Besnoy, & Steel, 2012). Therefore, the purpose of this research was to develop an understanding of pre-service teachers’ beliefs in regards to their abilities to effectively teach ELLs. Analyses of this research revealed significant differences between pre-service teachers who have and have not completed English for Speakers of Other Languages (ESOL) coursework. Pre-service teachers also reported linguistic barriers as the greatest barrier faced when educating ELLs.